2020
DOI: 10.32615/ps.2020.074
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic machinery and antioxidant status of wheat genotypes under drought stress followed by rewatering

Abstract: Land plants shorten their vegetation period during water deficiency. Under water stress, wheat plants undergo several changes at the morphophysiological level. We tried to elucidate the role of the morphophysiological parameters and the photosynthetic machinery in response to drought followed by rewatering. Therefore, some morphophysiological traits of two bread wheat genotypes (drought-tolerant Gobustan, drought-sensitive Tale 38) were studied. The H2O2 content increased under drought in both genotypes but re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…40 The dynamic interaction among ROS, the antioxidant system and thylakoid membranes under drought stress was found to be very important for the regulation of wheat photosynthesis under drought stress. 14 In this study, the activities of SOD and POD in winter wheat leaves increased during drought, and the contents of Pro and SS also increased significantly. This showed that the physiological mechanisms of crop resistance positively responded to weaken the adverse effects of drought on the photosynthetic environment.…”
Section: Relationship Between Photosynthetic Traits and Drought Resis...supporting
confidence: 52%
See 3 more Smart Citations
“…40 The dynamic interaction among ROS, the antioxidant system and thylakoid membranes under drought stress was found to be very important for the regulation of wheat photosynthesis under drought stress. 14 In this study, the activities of SOD and POD in winter wheat leaves increased during drought, and the contents of Pro and SS also increased significantly. This showed that the physiological mechanisms of crop resistance positively responded to weaken the adverse effects of drought on the photosynthetic environment.…”
Section: Relationship Between Photosynthetic Traits and Drought Resis...supporting
confidence: 52%
“…The RWC data were not measured in this study. However, other studies have shown that the RWC of wheat within the moisture range 30–60% FC was approximately 70–100% by examining two varieties with different degrees of drought tolerance 14 . The lowest soil moisture in this study was 45% FC, so it was hypothesized that the RWC should be some distance away from 70%.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Plants harmonize light harvesting, electron transport, and protein synthesis by adjusting the thylakoid membrane proteome in response to changes in the light environment [ 19 , 20 ]. The PsbS protein of PSII, responsible for qE, is also involved in the reorganization of the thylakoid membrane [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%